2009
DOI: 10.1086/605473
|View full text |Cite
|
Sign up to set email alerts
|

Population‐Based Incidence and Etiology of Community‐Acquired Neonatal Bacteremia in Mirzapur, Bangladesh: An Observational Study

Abstract: Background To devise treatment strategies for neonatal infections, the population-level incidence and antibiotic susceptibility of pathogens must be defined. Methods Surveillance for suspected neonatal sepsis was conducted in Mirzapur, Bangladesh, from February 2004 through November 2006. Community health workers assessed neonates on postnatal days 0, 2, 5, and 8 and referred sick neonates to a hospital, where blood was collected for culture from neonates with suspected sepsis. We estimated the incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 39 publications
4
82
2
Order By: Relevance
“…The number of positive cultures included in each study varied from 3030 31 to 784 12. Five studies (four from Africa and one from India) provided data for 72% of all positive isolates included in the review (2914 of 4049) 12 21 23 28 35…”
Section: Resultsmentioning
confidence: 99%
“…The number of positive cultures included in each study varied from 3030 31 to 784 12. Five studies (four from Africa and one from India) provided data for 72% of all positive isolates included in the review (2914 of 4049) 12 21 23 28 35…”
Section: Resultsmentioning
confidence: 99%
“…SMX-TMP is a combination of sulfamethoxazole (SMX) and trimethoprim (TMP) that is used for the treatment of protozoan and bacterial infections, particularly for urinary and respiratory tract infections (Darmstadt et al, 2009; Ladhani & Garbash, 2005; Ogra & Faden, 1985; Paap & Nahata, 1990; Salter, 1982; Thaver et al, 2009; Velvis et al, 1986). This combination is extensively used in the home--based neonate care setting in developing countries for treating pneumonia and sepsis in neonates (Bang et al, 1993, 1999; Bhutta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There have been rela vely few studies from India repor ng specifi c rates of EONS. A study from a home based surveillance program from Bangladesh reported the clinical EONS to be 50 per 1000 live births and that of blood cultureconfi rmed EONS, 2.9 per 1000 live births 22 .…”
Section: Discussionmentioning
confidence: 99%